2018
DOI: 10.1155/2018/4389484
|View full text |Cite
|
Sign up to set email alerts
|

2‐Methoxyestradiol Attenuates Testosterone‐Induced Benign Prostate Hyperplasia in Rats through Inhibition of HIF‐1α/TGF‐β/Smad2 Axis

Abstract: Benign prostatic hyperplasia (BPH) is a common disorder in the male population. 2-Methoxyestradiol (2ME) is an end metabolite of estrogens with pleiotropic pharmacological properties. This study aimed to explore the potential ameliorative effects of 2ME against testosterone-induced BPH in rats. 2-Methoxyestradiol (50 and 100 mg/kg, dissolved in DMSO) prevented the rise in prostatic index and weight in comparison to testosterone-alone-treated animals for 2 weeks. Histological examination indicated that 2ME amel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 57 publications
6
17
0
Order By: Relevance
“…Cyclin D1 is involved in regulating cell proliferation and its abundance is commonly interpreted in favor of cell division ( Fu et al, 2004 ). In line with previous studies ( Abdel-Naim et al, 2018 ; Basha et al, 2019 ), our data indicated that testosterone significantly enhanced cyclin D1 expression. However, PIC SNEDDS successfully hampered the raised cyclin D1 expression as detected immunohistochemically.…”
Section: Discussionsupporting
confidence: 93%
“…Cyclin D1 is involved in regulating cell proliferation and its abundance is commonly interpreted in favor of cell division ( Fu et al, 2004 ). In line with previous studies ( Abdel-Naim et al, 2018 ; Basha et al, 2019 ), our data indicated that testosterone significantly enhanced cyclin D1 expression. However, PIC SNEDDS successfully hampered the raised cyclin D1 expression as detected immunohistochemically.…”
Section: Discussionsupporting
confidence: 93%
“…The normal group (group 1) was not administered any treatment or testosterone. The remaining five groups were treated with 3 mg/kg testosterone enanthate subcutaneously (SC) five days a week for two weeks for BPH induction [35]. One control group (group 2) only received 3 mg/kg testosterone enanthate subcutaneously (SC) five days a week for two weeks.…”
Section: Design Of In Vivo Study Protocol For the Evaluation Of Tdl-pmentioning
confidence: 99%
“…Oxidative stress has been highly associated with the onset of several inflammatory pathologies occurring in elderly people, including periodontitis, osteoporosis, and metabolic disorders [12,15,16]. Also, clinical and experimental studies have a confirmed oxidative stress as a key contributor to the pathogenesis of BPH [17][18][19][20]. Moreover, compensatory cellular proliferation may be triggered by oxidative stress, which eventually leads to the growth of hyperplastic prostate tissue, whereas the factors that induce a more oxidative state in the prostate remain unclear.…”
Section: Introductionmentioning
confidence: 99%